Bracket Loaded Webs with Low Slenderness Ratios - Hopper, Bruce E.; Batson, Gordon B.; Ainso, Heino (Engineering Journal, 1985)
Welded bracket connections to the web of rolled sections are common connections. However, the AISC Manual of Steel Construction has no guidelines for estimating their capacity. Generally, the maximum load corresponds to the development of a two-dimensional yield mechanism in the web; but for sections whose webs have significant thickness relative to the T-distance, the maximum load may occur in the flanges. Abolitz and Warner conducted a theoretical investigation into bending of seated connections. By applying work methods to several yield line patterns, they developed an expression for the lowest value of the ultimate load.